Genotoxicity assessment of raw and treated water samples using Allium cepa assay: evidence from Perak River, Malaysia - Malakahmad, A. (Springer Verlag, 2018)
Allium cepa assay was carried out in this study to evaluate genotoxic effects of raw and treated water samples from Perak River in Perak state, Malaysia. Samples were collected from three surface water treatment plants along the river, namely WTPP, WTPS, and WTPK. Initially, triplicates of equal size Allium cepa (onions) bulbs, 25â30Â mm in diameter and average weight of 20Â g, were set up in distilled water for 24Â h at 20 Â± 2Â Â°C and protected from direct sunlight, to let the roots to grow. After germination of roots (0.5â1.0Â cm in length), bulbs were transferred to collected water samples each for a 96-h period of exposure. The root physical deformations were observed. Genotoxicity quantification was based on mitotic index and genotoxicity level. Statistical analysis using cross-correlation function for replicates from treated water showed that root length has inverse correlation with mitotic indices (r = â 0.969) and frequencies of cell aberrations (r = â 0.976) at lag 1. Mitotic indices and cell aberrations of replicates from raw water have shown positive correlation at lag 1 (r = 0.946). Genotoxicity levels obtained were 23.4 Â± 1.98 (WTPP), 26.68 Â± 0.34 (WTPS), and 30.4 Â± 1.13 (WTPK) for treated water and 17.8 Â± 0.18 (WTPP), 37.15 Â± 0.17 (WTPS), and 47.2 Â± 0.48 (WTPK) for raw water. The observed cell aberrations were adherence, chromosome delay, C-metaphase, chromosome loss, chromosome bridge, chromosome breaks, binucleated cell, mini cell, and lobulated nuclei. The morphogenetic deformations obtained were likely due to genotoxic substances presence in collected water samples. Thus, water treatment in Malaysia does not remove genotoxic compounds. Â© 2017, Springer-Verlag GmbH Germany, part of Springer Nature.